Analysis of climate and anthropogenic impacts on runoff in the Lower Pra River Basin of Ghana. Issue 12 (December 2017) - Awotwi, Alfred; Anornu, Geophrey Kwame; Quaye-Ballard, Jonathan; Annor, Thompson; Forkuo, Eric Kwabena
Abstract: The Lower Pra River Basin (LPRB), located in the forest zone of southern Ghana has experienced changes due to variability in precipitation and diverse anthropogenic activities. Therefore, to maintain the functions of the ecosystem for water resources management, planning and sustainable development, it is important to differentiate the impacts of precipitation variability and anthropogenic activities on stream flow changes. We investigated the variability in runoff and quantified the contributions of precipitation and anthropogenic activities on runoff at the LPRB. Analysis of the precipitation–runoff for the period 1970–2010 revealed breakpoints in 1986, 2000, 2004 and 2010 in the LPRB. The periods influenced by anthropogenic activities were categorized into three periods 1987–2000, 2001–2004 and 2005–2010, revealing a decrease in runoff during 1987–2000 and an increase in runoff during 2001–2004 and 2005–2010. Assessment of monthly, seasonal and annual runoff depicted a significant increasing trend in the runoff time series during the dry season. Generally, runoff increased at a rate of 9.98 × 10 7 m 3 yr −1, with precipitation variability and human activities contributing 17.4% and 82.3% respectively. The dominant small scale alluvial gold mining activity significantly contributes to the net runoff variability in LPRB.